Self-healing spraying material for micro-cracks on surface of mass concrete and preparation process of self-healing spraying material
By using sodium silicate and calcium ions on large volume concrete surfaces to generate calcium silicate gels, combined with microencapsulation technology and dynamic reversible chemical bonds, the problem of repairing microcracks on the concrete surface is solved, the stability and self-healing ability of the material are improved, and the ability of the material is adapted to extreme environments.
Patent Information
- Application Number
- CN202411869291.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-04
AI Technical Summary
Large volume concrete is prone to surface microcracks during construction and use, which affects its appearance and structural safety. In addition, the activity of existing self-healing spray materials is inhibited in extreme environments, and lacks adhesion and durability.
Silicon oxygen bonds are generated by hydrolysis of sodium silicate and calcium silicate gels are generated with calcium ions to repair cracks. Microencapsulated sodium silicate is used to control the release, improving stability and repair efficiency; dynamic reversible chemical bonds and temperature-sensitive materials are introduced into silicone resins to enhance the adhesion and self-healing ability of the material.
It realizes rapid repair and filling when cracks appear, improves the stability and repair efficiency of the material, enhances adhesion and durability, and adapts to self-healing performance in extreme environments.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building material preparation, and relates to a self-healing spray material for micro-cracks on the surface of a large volume of concrete and a preparation process thereof. Background Art
[0002] During the construction and use of large-volume concrete, due to its large volume and complex environmental conditions, it is often affected by multiple factors such as temperature stress, shrinkage stress and chemical erosion, which leads to the generation of surface microcracks. In the early stage of concrete hardening, the cement hydration reaction will release a lot of heat, causing the internal temperature to rise. When the internal temperature gradually drops, tensile stress will be generated on the surface of the concrete due to the temperature gradient. If these stresses exceed the tensile strength of the concrete, microcracks will form. In addition, the concrete will shrink in volume during the drying process. Especially in the case of improper early maintenance, the rapid loss of water on the surface will also lead to the appearance of microcracks. The existence of microcracks not only affects the appearance of concrete, but also becomes a channel for the invasion of harmful substances from the outside, accelerating the corrosion of steel bars and the deterioration of concrete. In severe cases, it even affects the safety and durability of the structure.
[0003] In order to effectively solve the problem of micro cracks on the surface of large-volume concrete, the development of self-healing spray materials has become an important technical means. The main function of this material is to automatically repair cracks when they appear, thereby preventing further expansion of cracks and the invasion of harmful substances. Self-healing spray materials usually contain active ingredients that can react chemically at the cracks, such as microencapsulated repair agents. These active ingredients are activated when cracks form, filling the cracks and restoring the integrity of the concrete. In this way, not only can the service life of concrete structures be extended, but the frequency and cost of maintenance and repair can also be reduced, which has significant economic and environmental benefits.
[0004] However, the current self-healing spray technology still has some shortcomings. First, many self-healing materials have limited healing speed and healing effect on cracks in practical applications, especially in extreme environments such as low temperature or high humidity, where the activity of the materials may be inhibited. Second, the adhesion and durability of the sprayed materials need to be further improved to ensure their long-term effectiveness on the concrete surface. Summary of the invention
[0005] The present invention relates to a self-healing spray material for micro-cracks on the surface of large-volume concrete and a preparation process thereof, and belongs to the field of building material preparation. The present invention utilizes sodium silicate to hydrolyze to generate silicic acid and then condense to form silicon-oxygen bonds, and generates calcium silicate gel with calcium ions to repair cracks, and controls the release of microencapsulated sodium silicate to improve stability and repair efficiency; dynamic reversible chemical bonds and temperature-sensitive materials are introduced into silicone resin to enhance the adhesion of the material and strengthen the fracture repair ability.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A self-healing spraying material for micro-cracks on the surface of a large volume of concrete comprises the following components in parts by weight: 30-40 parts by weight of sodium silicate, 1-8 parts by weight of an emulsifier, 15-20 parts by weight of a polymer, 5-10 parts by weight of nano-barium titanate, 5-8 parts by weight of calcium chloride, 20-30 parts by weight of a modified silicone resin, 0.5-1 parts by weight of a dispersant, 1-2 parts by weight of a sulfuric acid solution and 10-20 parts by weight of deionized water.
[0008] As a preferred technical solution of the present invention, the emulsifier is at least one of Tween 80 and Span 80.
[0009] As a preferred technical solution of the present invention, the polymer is polylactic acid or polyurethane.
[0010] As a preferred technical solution of the present invention, the preparation method of the modified silicone resin is: dissolving the dynamic reversible chemical bond monomer in a solvent, adding it to the silicone resin and adding an organic silane coupling agent, reacting at 60-80°C for 4-8h, adding a temperature-sensitive material and mixing evenly, and then removing the solvent by reduced pressure distillation.
[0011] As a preferred technical solution of the present invention, the dynamically reversible chemical bond monomer is 2,2'-dithiodibenzoic acid or diphenyl disulfide, the solvent is anhydrous ethanol or toluene, and the temperature-sensitive material is poly (N-isopropylacrylamide); the mass ratio of the dynamically reversible chemical bond monomer, solvent, silicone resin, organic silane coupling agent, and temperature-sensitive material is 1:8-12:8-12:0.1-0.2:1-3.
[0012] As a preferred technical solution of the present invention, the dispersant is sodium polyacrylate.
[0013] As a preferred technical solution of the present invention, the concentration of the dilute sulfuric acid solution is 4 mol / L.
[0014] Furthermore, the method for preparing the self-healing spraying material for micro-cracks on the surface of large-volume concrete comprises the following steps:
[0015] (1) adding sodium silicate to deionized water, stirring evenly, adding an emulsifier, and stirring at 1000-3000 rpm for 5-30 minutes using a high-speed stirrer to form sodium silicate emulsion droplets;
[0016] (2) dissolving the polymer in dichloromethane or ethyl acetate to form a coating material solution;
[0017] (3) under continuous stirring, adding the coating material solution dropwise into the sodium silicate emulsion droplets to form microcapsules, and then spray drying to obtain microcapsule powder;
[0018] (4) mixing the microcapsule powder, nano-barium titanate and calcium chloride, using a high shear mixer to ensure uniform distribution, adding the modified silicone resin, and stirring to form a mixed material;
[0019] (5) Disperse the mixed material in deionized water, add a dispersant, adjust the pH value to 6.0-8.0 with sulfuric acid solution, and seal for storage.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention prepares a sodium silicate solution into microcapsules for crack repair, which can break under specific conditions (such as when cracks appear) to release sodium silicate, thereby controlling its release rate, which helps to provide repair materials in time at the early stage of crack appearance. In addition, the microcapsules can accurately release sodium silicate at the cracks, ensuring that it fully reacts with calcium ions to generate calcium silicate gel, which quickly fills and repairs the cracks.
[0022] (2) The modified resin of the present invention with the addition of dynamic reversible chemical bonds can significantly improve the self-healing ability. Dynamic reversible chemical bonds can self-repair cracks by reorganizing chemical bonds after the cracks are generated, thereby restoring the integrity and function of the structure. Silicone resin also improves weather resistance and durability, thereby promoting the reorganization and self-healing process of dynamic reversible chemical bonds when the temperature rises. When the temperature-sensitive material N-isopropylacrylamide is added, when cracks appear, the increase in temperature will promote the enhancement of the hydrophobic interaction of N-isopropylacrylamide, the molecular chains will aggregate and rearrange, filling the crack area, thereby achieving self-healing. DETAILED DESCRIPTION
[0023] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0024] In the following embodiments and comparative examples, the polylactic acid was purchased from Suzhou Jiangcangfa Plastics Co., Ltd. with the brand name REVODE201; polyurethane was purchased from Anhui Dawei Huatai New Materials Technology Co., Ltd. with the model number AH-K100-1; silicone resin was purchased from Laiyang Shengbang Silicone Technology Co., Ltd. with the model number 102; organosilane coupling agent was purchased from Longchen Chemical Industry Bank, Guancheng Hui Autonomous District, Zhengzhou City, with the single product number 01-067; sodium polyacrylate was purchased from Zhongtai Lianhua New Materials Co., Ltd. with the model number AG-22.
[0025] Example 1
[0026] A self-healing spray material for micro-cracks on the surface of a large volume of concrete comprises the following components in parts by weight: 35 parts by weight of sodium silicate, 5 parts by weight of an emulsifier, 18 parts by weight of a polymer, 8 parts by weight of nano-barium titanate, 6 parts by weight of calcium chloride, 25 parts by weight of a modified silicone resin, 0.8 parts by weight of a dispersant, 1.5 parts by weight of a sulfuric acid solution and 15 parts by weight of deionized water.
[0027] The emulsifier is Tween 80.
[0028] The polymer is polylactic acid.
[0029] The preparation method of the modified silicone resin is as follows: dissolving a dynamic reversible chemical bond monomer in a solvent, adding the monomer to the silicone resin and adding an organic silane coupling agent, reacting the mixture at 70° C. for 6 hours, adding a temperature-sensitive material, mixing the mixture evenly, and removing the solvent by reduced pressure distillation.
[0030] The dynamic reversible chemical bond monomer is 2,2'-dithiodibenzoic acid, the solvent is anhydrous ethanol, and the temperature-sensitive material is poly (N-isopropylacrylamide); the mass ratio of the dynamic reversible chemical bond monomer, the solvent, the silicone resin, the organic silane coupling agent, and the temperature-sensitive material is 1:10:10:0.15:2.
[0031] The dispersant is sodium polyacrylate.
[0032] The concentration of the dilute sulfuric acid solution is 4 mol / L.
[0033] The method for preparing a self-healing spray material for micro-cracks on the surface of a large volume of concrete comprises the following steps:
[0034] (1) adding sodium silicate to deionized water, stirring evenly, adding an emulsifier, and stirring at 2000 rpm for 20 min using a high-speed stirrer to form sodium silicate emulsion droplets;
[0035] (2) dissolving the polymer in dichloromethane or ethyl acetate to form a coating material solution;
[0036] (3) under continuous stirring, adding the coating material solution dropwise into the sodium silicate emulsion droplets to form microcapsules, and then spray drying to obtain microcapsule powder;
[0037] (4) mixing the microcapsule powder, nano-barium titanate and calcium chloride, using a high shear mixer to ensure uniform distribution, adding the modified silicone resin, and stirring to form a mixed material;
[0038] (5) Disperse the mixed material in deionized water, add a dispersant, adjust the pH value to 7.0 with sulfuric acid solution, and seal for storage.
[0039] Example 2
[0040] A self-healing spray material for micro-cracks on the surface of a large volume of concrete comprises the following components in parts by weight: 30 parts by weight of sodium silicate, 1 part by weight of an emulsifier, 15 parts by weight of a polymer, 5 parts by weight of nano-barium titanate, 5 parts by weight of calcium chloride, 20 parts by weight of a modified silicone resin, 0.5 parts by weight of a dispersant, 1 part by weight of a sulfuric acid solution and 10 parts by weight of deionized water.
[0041] The emulsifier is Tween 80.
[0042] The polymer is polylactic acid.
[0043] The preparation method of the modified silicone resin is as follows: dissolving a dynamic reversible chemical bond monomer in a solvent, adding the monomer to the silicone resin and adding an organic silane coupling agent, reacting the mixture at 60° C. for 8 hours, adding a temperature-sensitive material and mixing the mixture evenly, and removing the solvent by reduced pressure distillation.
[0044] The dynamic reversible chemical bond monomer is 2,2'-dithiodibenzoic acid, the solvent is anhydrous ethanol, and the temperature-sensitive material is poly (N-isopropylacrylamide); the mass ratio of the dynamic reversible chemical bond monomer, the solvent, the silicone resin, the organic silane coupling agent, and the temperature-sensitive material is 1:8:8:0.1:1.
[0045] The dispersant is sodium polyacrylate.
[0046] The concentration of the dilute sulfuric acid solution is 4 mol / L.
[0047] The method for preparing a self-healing spray material for micro-cracks on the surface of a large volume of concrete comprises the following steps:
[0048] (1) adding sodium silicate to deionized water, stirring evenly, adding an emulsifier, and stirring at 1000 rpm for 30 min using a high-speed stirrer to form sodium silicate emulsion droplets;
[0049] (2) dissolving the polymer in dichloromethane or ethyl acetate to form a coating material solution;
[0050] (3) under continuous stirring, adding the coating material solution dropwise into the sodium silicate emulsion droplets to form microcapsules, and then spray drying to obtain microcapsule powder;
[0051] (4) mixing the microcapsule powder, nano-barium titanate and calcium chloride, using a high shear mixer to ensure uniform distribution, adding the modified silicone resin, and stirring to form a mixed material;
[0052] (5) Disperse the mixed material in deionized water, add a dispersant, adjust the pH value to 6.0 with sulfuric acid solution, and seal for storage.
[0053] Example 3
[0054] A self-healing spray material for micro-cracks on the surface of a large volume of concrete comprises the following components in parts by weight: 40 parts by weight of sodium silicate, 8 parts by weight of an emulsifier, 20 parts by weight of a polymer, 10 parts by weight of nano-barium titanate, 8 parts by weight of calcium chloride, 30 parts by weight of a modified silicone resin, 1 part by weight of a dispersant, 2 parts by weight of a sulfuric acid solution and 20 parts by weight of deionized water.
[0055] The emulsifier is Span 80.
[0056] The polymer is polyurethane.
[0057] The preparation method of the modified silicone resin is as follows: dissolving a dynamic reversible chemical bond monomer in a solvent, adding the monomer to the silicone resin and adding an organic silane coupling agent, reacting the mixture at 80° C. for 4 hours, adding a temperature-sensitive material and mixing the mixture evenly, and removing the solvent by reduced pressure distillation.
[0058] The dynamic reversible chemical bond monomer is diphenyl disulfide, the solvent is toluene, and the temperature-sensitive material is poly (N-isopropylacrylamide); the mass ratio of the dynamic reversible chemical bond monomer, the solvent, the silicone resin, the organic silane coupling agent, and the temperature-sensitive material is 1:12:12:0.2:3.
[0059] The dispersant is sodium polyacrylate.
[0060] The concentration of the dilute sulfuric acid solution is 4 mol / L.
[0061] The method for preparing a self-healing spray material for micro-cracks on the surface of a large volume of concrete comprises the following steps:
[0062] (1) adding sodium silicate to deionized water, stirring evenly, adding an emulsifier, and stirring at 3000 rpm for 5 min using a high-speed stirrer to form sodium silicate emulsion droplets;
[0063] (2) dissolving the polymer in dichloromethane or ethyl acetate to form a coating material solution;
[0064] (3) under continuous stirring, adding the coating material solution dropwise into the sodium silicate emulsion droplets to form microcapsules, and then spray drying to obtain microcapsule powder;
[0065] (4) mixing the microcapsule powder, nano-barium titanate and calcium chloride, using a high shear mixer to ensure uniform distribution, adding the modified silicone resin, and stirring to form a mixed material;
[0066] (5) Disperse the mixed material in deionized water, add a dispersant, adjust the pH value to 8.0 with sulfuric acid solution, and seal for storage.
[0067] Example 4
[0068] A self-healing spray material for micro-cracks on the surface of a large volume of concrete comprises the following components in parts by weight: 40 parts by weight of sodium silicate, 8 parts by weight of an emulsifier, 15 parts by weight of a polymer, 5 parts by weight of nano-barium titanate, 8 parts by weight of calcium chloride, 20 parts by weight of a modified silicone resin, 1 part by weight of a dispersant, 2 parts by weight of a sulfuric acid solution and 20 parts by weight of deionized water.
[0069] The emulsifier is Span 80.
[0070] The polymer is polyurethane.
[0071] The preparation method of the modified silicone resin is as follows: dissolving a dynamic reversible chemical bond monomer in a solvent, adding the monomer to the silicone resin and adding an organic silane coupling agent, reacting the mixture at 60° C. for 4 hours, adding a temperature-sensitive material and mixing the mixture evenly, and removing the solvent by reduced pressure distillation.
[0072] The dynamic reversible chemical bond monomer is diphenyl disulfide, the solvent is toluene, and the temperature-sensitive material is poly (N-isopropylacrylamide); the mass ratio of the dynamic reversible chemical bond monomer, the solvent, the silicone resin, the organic silane coupling agent, and the temperature-sensitive material is 1:12:8:0.2:1.
[0073] The dispersant is sodium polyacrylate.
[0074] The concentration of the dilute sulfuric acid solution is 4 mol / L.
[0075] The method for preparing a self-healing spray material for micro-cracks on the surface of a large volume of concrete comprises the following steps:
[0076] (1) adding sodium silicate to deionized water, stirring evenly, adding an emulsifier, and stirring at 1000 rpm for 5 min using a high-speed stirrer to form sodium silicate emulsion droplets;
[0077] (2) dissolving the polymer in dichloromethane or ethyl acetate to form a coating material solution;
[0078] (3) under continuous stirring, adding the coating material solution dropwise into the sodium silicate emulsion droplets to form microcapsules, and then spray drying to obtain microcapsule powder;
[0079] (4) mixing the microcapsule powder, nano-barium titanate and calcium chloride, using a high shear mixer to ensure uniform distribution, adding the modified silicone resin, and stirring to form a mixed material;
[0080] (5) Disperse the mixed material in deionized water, add a dispersant, adjust the pH value to 6.5 with sulfuric acid solution, and seal for storage.
[0081] Comparative Example 1
[0082] A self-healing spray material for micro-cracks on the surface of a large volume of concrete comprises the following components in parts by weight: 35 parts by weight of sodium silicate, 8 parts by weight of nano-barium titanate, 6 parts by weight of calcium chloride, 25 parts by weight of modified silicone resin, 0.8 parts by weight of dispersant, 1.5 parts by weight of sulfuric acid solution and 15 parts by weight of deionized water.
[0083] The preparation method of the modified silicone resin is as follows: dissolving a dynamic reversible chemical bond monomer in a solvent, adding the monomer to the silicone resin and adding an organic silane coupling agent, reacting the mixture at 70° C. for 6 hours, adding a temperature-sensitive material, mixing the mixture evenly, and removing the solvent by reduced pressure distillation.
[0084] The dynamic reversible chemical bond monomer is 2,2'-dithiodibenzoic acid, the solvent is anhydrous ethanol, and the temperature-sensitive material is poly (N-isopropylacrylamide); the mass ratio of the dynamic reversible chemical bond monomer, the solvent, the silicone resin, the organic silane coupling agent, and the temperature-sensitive material is 1:10:10:0.15:2.
[0085] The dispersant is sodium polyacrylate.
[0086] The concentration of the dilute sulfuric acid solution is 4 mol / L.
[0087] The method for preparing a self-healing spray material for micro-cracks on the surface of a large volume of concrete comprises the following steps:
[0088] (1) Sodium silicate, nano-barium titanate and calcium chloride are mixed, and after ensuring uniform distribution using a high shear mixer, modified silicone resin is added and stirred to form a mixed material;
[0089] (2) Disperse the mixed material in deionized water, add a dispersant, adjust the pH value to 7.0 with sulfuric acid solution, and seal for storage.
[0090] Comparative Example 2
[0091] A self-healing spray material for micro-cracks on the surface of a large volume of concrete comprises the following components in parts by weight: 35 parts by weight of sodium silicate, 5 parts by weight of an emulsifier, 18 parts by weight of a polymer, 8 parts by weight of nano-barium titanate, 6 parts by weight of calcium chloride, 25 parts by weight of a silicone resin, 0.8 parts by weight of a dispersant, 1.5 parts by weight of a sulfuric acid solution and 15 parts by weight of deionized water.
[0092] The emulsifier is Tween 80.
[0093] The polymer is polylactic acid.
[0094] The dispersant is sodium polyacrylate.
[0095] The concentration of the dilute sulfuric acid solution is 4 mol / L.
[0096] The method for preparing a self-healing spray material for micro-cracks on the surface of a large volume of concrete comprises the following steps:
[0097] (1) adding sodium silicate to deionized water, stirring evenly, adding an emulsifier, and stirring at 2000 rpm for 20 min using a high-speed stirrer to form sodium silicate emulsion droplets;
[0098] (2) dissolving the polymer in dichloromethane or ethyl acetate to form a coating material solution;
[0099] (3) under continuous stirring, adding the coating material solution dropwise into the sodium silicate emulsion droplets to form microcapsules, and then spray drying to obtain microcapsule powder;
[0100] (4) mixing the microcapsule powder, nano-barium titanate and calcium chloride, using a high shear mixer to ensure uniform distribution, adding silicone resin, and stirring to form a mixed material;
[0101] (5) Disperse the mixed material in deionized water, add a dispersant, adjust the pH value to 7.0 with sulfuric acid solution, and seal for storage.
[0102] Performance Test:
[0103] Refer to GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" to test the repair rate of the test area;
[0104] Referring to GB / T 50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", the impermeability grade of Examples 1-3 and the blank sample was tested, and the higher the grade, the better the impermeability effect;
[0105] Area repair rate Impermeability grade Not sprayed 0 P4 Example 1 98.3% P12 Example 2 97.6% P12 Example 3 97.1% P12 Example 4 96.8% P12 Comparative Example 1 84.3% P9 Comparative Example 2 82.7% P8
[0106] The test results show that the self-healing spray material prepared by the present invention has an effective area repair rate of more than 96% after being sprayed on the surface of large-volume concrete, and the impermeability grade is improved from P4 to P12 high impermeability concrete level.
[0107] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any indirect modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A self-healing spray material for micro cracks on the surface of large-volume concrete, characterized by: The invention comprises the following components in parts by weight: 30-40 parts by weight of sodium silicate, 1-8 parts by weight of emulsifier, 15-20 parts by weight of polymer, 5-10 parts by weight of nano barium titanate, 5-8 parts by weight of calcium chloride, 20-30 parts by weight of modified silicone resin, 0.5-1 parts by weight of dispersant, 1-2 parts by weight of sulfuric acid solution and 10-20 parts by weight of deionized water.
2. The self-healing spray material for micro-cracks on the surface of large-volume concrete according to claim 1, characterized in that: The emulsifier is at least one of Tween 80 and Span 80.
3. The self-healing spray material for micro-cracks on the surface of large-volume concrete according to claim 1, characterized in that: The polymer is polylactic acid or polyurethane.
4. The self-healing spray material for micro-cracks on the surface of large-volume concrete according to claim 1, characterized in that: The preparation method of the modified silicone resin is as follows: dissolving a dynamic reversible chemical bond monomer in a solvent, adding the monomer to the silicone resin and adding an organic silane coupling agent, reacting at 60-80° C. for 4-8 hours, adding a temperature-sensitive material and mixing evenly, and removing the solvent by reduced pressure distillation.
5. The self-healing spray material for micro-cracks on the surface of large-volume concrete according to claim 4, characterized in that: The dynamic reversible chemical bond monomer is 2,2'-dithiodibenzoic acid or diphenyl disulfide, the solvent is anhydrous ethanol or toluene, and the temperature-sensitive material is poly (N-isopropylacrylamide); the mass ratio of the dynamic reversible chemical bond monomer, solvent, silicone resin, organic silane coupling agent, and temperature-sensitive material is 1:8-12:8-12:0.1-0.2:1-3.
6. The self-healing spray material for micro-cracks on the surface of large-volume concrete according to claim 1, characterized in that: The dispersant is sodium polyacrylate.
7. The self-healing spray material for micro-cracks on the surface of large-volume concrete according to claim 1, characterized in that: The concentration of the dilute sulfuric acid solution is 4 mol / L.
8. A method for preparing the self-healing spraying material for micro-cracks on the surface of mass concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) adding sodium silicate to deionized water, stirring evenly, adding an emulsifier, and stirring at 1000-3000 rpm for 5-30 minutes using a high-speed stirrer to form sodium silicate emulsion droplets; (2) dissolving the polymer in dichloromethane or ethyl acetate to form a coating material solution; (3) under continuous stirring, adding the coating material solution dropwise into the sodium silicate emulsion droplets to form microcapsules, and then spray drying to obtain microcapsule powder; (4) mixing the microcapsule powder, nano-barium titanate and calcium chloride, using a high shear mixer to ensure uniform distribution, adding the modified silicone resin, and stirring to form a mixed material; (5) Disperse the mixed material in deionized water, add a dispersant, adjust the pH value to 6.0-8.0 with sulfuric acid solution, and seal for storage.